La sorpresa en la experiencia estética de la música popular - Cercado, Antonio (Pontificia Universidad Católica del Perú, 2024)
Popular music has used new technologies and the globalizing nature of our time to expand into different species of daily life. We live overstimulated by different rhythms, melodies and sounds. In this diverse context, how do we explain that we like something new? In what follows, we propose to explain the genesis of taste, starting from the temporal structure of surprise proposed by Natalie Depraz: anticipation-impression-resonance. The idea is to understand taste as a possibility of surprise; as a resonance of the first sound experience. In this way, a different perspective on the aesthetics of taste can be offered: outside or differentiating itself from established aesthetic models. Furthermore, it will be possible to understand how surprise participates in the origin of the different musical communities that are responsible for sustaining mass musical productions.

La música popular se ha servido de nuevas tecnologías y del carácter globalizador de nuestra época para expandirse por diferentes espacios de la vida cotidiana. Vivimos sobre estimulados por diferentes ritmos, melodías y sonidos. En este contexto tan diverso, ¿cómo explicamos que algo nuevo nos guste? La propuesta de este trabajo es explicar la génesis del gusto, partiendo de la estructura temporal de la sorpresa propuesta por Natalie Depraz: anticipación-impresión-resonancia. La idea es entender el gusto como una posibilidad de la sorpresa; como resonancia de la primera experiencia sonora. De esta forma, se podrá ofrecer una perspectiva distinta de la estética del gusto: fuera o diferenciándose de los modelos estéticos establecidos. Además, se podrá entender cómo la sorpresa participa en el origen de las distintas comunidades musicales que son responsables de sostener la producción musical masiva.
Keywords: Music; Time; Surprise; Aesthetics; Identity; Música; Tiempo; Sorpresa; Estética; Identidad; https://purl.org/pe-repo/ocde/ford#6.03.01